Developing University Students’ Speaking Skill through Metacognitive Strategies - Sari, Pradita Resdiana; Sinaga, Juwita Boneka; Ashari, Erwin (Lectura : Jurnal Pendidikan, 2025)
Speaking is a critical communication skill that requires real-time cognitive and metacognitive processes. Metacognitive strategies, including planning, monitoring, and evaluation, have been recognized for their role in enhancing language skills and fostering learner autonomy. Despite extensive studies on language learning strategies, their specific impact on speaking proficiency remains underexplored. This study aims to investigate the role of metacognitive strategies in improving the speaking skills of first-semester students. It also seeks to explore how these strategies can foster learner autonomy and reduce speaking-related anxiety. A quasi-experimental design was employed, involving 30 first semester EFL students divided into experimental and control groups. The experimental group received explicit training in metacognitive strategies, while the control group followed traditional speaking practices. The results revealed significant improvements in the experimental group’s speaking proficiency, particularly in fluency, pronunciation, and vocabulary use. The experimental group also demonstrated higher levels of self-awareness and confidence compared to the control group. These outcomes substantiate the effectiveness of metacognitive strategies in enhancing speaking skills and promoting learner autonomy. This study concludes that integrating metacognitive strategies into speaking instruction benefits learners by improving speaking proficiency and reducing anxiety. Incorporating these strategies into teaching practices can support learners in achieving greater autonomy and confidence in language acquisition.